2022
DOI: 10.3389/fpls.2021.807739
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Modulates the Landscape of Transcriptome and Alternative Splicing in Date Palm (Phoenix dactylifera L.)

Abstract: Date palm regards as a valuable genomic resource for exploring the tolerance genes due to its ability to survive under the sever condition. Although a large number of differentiated genes were identified in date palm responding to salt stress, the genome-wide study of alternative splicing (AS) landscape under salt stress conditions remains unknown. In the current study, we identified the stress-related genes through transcriptomic analysis to characterize their function under salt. A total of 17,169 genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
(103 reference statements)
3
8
0
1
Order By: Relevance
“…Results for relative dry weight % of different date palm cultivars in response to increasing salinity, dry weight % reduction was maximum for the plantlets of Halimi, Basrawali, Dhakki, Sanduri, Saghoi, Tarwali, Hamanwali, and Gajjar. Current findings on dry weight percentage are consistent with an earlier study by [23]. However, linear relationships between the decreases in dry weight of different tissues with an increase in salt concentration suggest that osmoregulation is effective for salt tolerance only to a limited range in the continuum of salt stress.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results for relative dry weight % of different date palm cultivars in response to increasing salinity, dry weight % reduction was maximum for the plantlets of Halimi, Basrawali, Dhakki, Sanduri, Saghoi, Tarwali, Hamanwali, and Gajjar. Current findings on dry weight percentage are consistent with an earlier study by [23]. However, linear relationships between the decreases in dry weight of different tissues with an increase in salt concentration suggest that osmoregulation is effective for salt tolerance only to a limited range in the continuum of salt stress.…”
Section: Discussionsupporting
confidence: 90%
“…After measuring fresh weight, plant materials were placed in a drying oven (Memmert-110, Schawabach) for drying at 72ºC for a week. After one week of drying, the dried biomass percentage was weighted on a digital balance, and the average dry weight percentage of each replicate was recorded and described by [23]. After that, the roots were separated from the whole plant.…”
Section: Measurements After Harvestingmentioning
confidence: 99%
“…1 (Wei et al, 2021;Wu et al, 2018). Chlorophyll accumulation is significantly reduced under salinity stress in various plant species through downregulating the expression of glutamyl-tRNA reductase (HEMA1), Mg-chelatase (CHLH) and protochlorophyllide oxidoreductase (Xu et al, 2021b). Likewise, another study reported that salinity stress reduces chlorophyll biosynthesis through downregulation enzymes and chlorophyll biosynthesis genes such as HEM1, CHLH and POR (Wu et al, 2018).…”
Section: Detrimental Effects Of Salinity Stress On Plants Detrimental...mentioning
confidence: 99%
“…Osmotic stress in the initial stage of salinity stress causes various physiological changes (Yang and Guo, 2018a;Zhao et al, 2021), such as interruption of membrane potentials, nutrient imbalance, impairment of the ability to detoxify ROS (Choudhury et al, 2017), unstable antioxidant enzyme activities, decreased photosynthetic capacity, and reduced size of stomatal apertures (Figure 1) (Wei et al, 2021). Increased accumulation of Na + and Cl − ions in tissues of plants (Al Hassan et al, 2016) causes severe ion imbalance and significant physiological disorders, and a large number of genes involved in the regulation of chlorophyll, photosynthesis, antioxidant enzymes, hormones, are upregulated in Phoenix dactylifera (Xu et al, 2021b).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that high salinity stress can promote the occurrence of alternative splicing of stress-responsive genes and affect the expression of the genes coding spliceosome components in Arabidopsis (Ding et al, 2014b;Feng et al, 2015;Gu et al, 2018), rice (Yu et al, 2021;Jian et al, 2022), wheat (Liu et al, 2018), Barley (Fu et al, 2019), Date Palm (Xu et al, 2021), grapevine (Jin et al, 2021), cotton (Zhu et al, 2018), Opisthopappus (Han et al, 2024), etc. However, the alternative splicing events in tomato root under salt stress remains to be resolved.…”
Section: Introductionmentioning
confidence: 99%